2016
DOI: 10.3390/nu8100638
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Athletes Seeking Nutrition Advice at a Major International Competition

Abstract: International travel and short-term residence overseas is now a common feature of an elite athlete’s competition schedule, however, food choice away from home may be challenging and potentially impact on performance. Guidelines for dietary intake specific to competition exist for athletes, however, there is little evidence available to ascertain if athletes meet these recommendations during competition periods, particularly when food is provided in-house. During the Delhi 2010 Commonwealth Games, dietitians ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…Mean energy intake in this group of female Australian rules football players was 7826 ± 2411 kJ⋅kg −1 , which is slightly below that reported in previous studies in Australian female athletes, with mean energy intakes ranging from 8674 kJ to 10,511 kJ⋅kg −1 [9,24,25]. The lower energy intake in the current investigation may be due to the nature of Australian rules football.…”
Section: Discussioncontrasting
confidence: 73%
“…Mean energy intake in this group of female Australian rules football players was 7826 ± 2411 kJ⋅kg −1 , which is slightly below that reported in previous studies in Australian female athletes, with mean energy intakes ranging from 8674 kJ to 10,511 kJ⋅kg −1 [9,24,25]. The lower energy intake in the current investigation may be due to the nature of Australian rules football.…”
Section: Discussioncontrasting
confidence: 73%
“…The foods athletes choose to eat can impact on their wellbeing and performance, body composition, gut comfort and fuel available for training, competition and recovery. Despite the key role diet has on health and performance, athletes may not make appropriate food choices [1][2][3]. There are a limited number of studies that have explored individual and interpersonal determinants of food choices in athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these general values, tailored recommendations are set for specific sport disciplines, such as endurance, team, and strength sports [ 8 , 9 , 10 ]. Although athletes are considered a disciplined and motivated population, several recent studies have suggested that athletes may often not meet macronutrient recommendations [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, this viewpoint has been questioned by others [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%